STUDENTS’ EXPERIENCE IN USING THE ELSA SPEAK APPLICATION AS ENGLISH LEARNING MEDIA FOR DEE STUDENTS - Sari, Dila Permata; Muamaroh (Fakultas Bahasa dan Sastra Universitas PGRI Kanjuruhan Malang, 2025)
This study aims to find out the reasons and experiences of 7th semester students in using ELSA Speak application as an English learning media. This research uses descriptive qualitative method involving 30 students of English Education Department Universitas Muhammadiyah Surakarta who have used ELSA Speak application consisting of 10 males and 20 females. Data was collected through an open questionnaire filled out by 30 students through Google Form and in-depth interviews were conducted with 10 students randomly using the spinner application, then the data was analyzed qualitatively thematically. The results found four reasons for students to use ELSA Speak, namely to improve students’ English speaking, to improve English pronunciation, recommended by lecturers, can be used flexibly. Meanwhile, there are five experiences felt by students, namely interactive and non-boring exercises, increasing students’ confidence in speaking English, knowing students’ progress directly, getting feedback, practicing speaking directly based on the AI roleplay feature.